The Greater Goal : Connecting Purpose and Performance. - Jennings, Ken (Kenneth R.) (BK business book., 2012)
The bestselling coauthor of The Serving Leader (over 90,000 copies sold) provides a roadmap that all leaders can use to create and align entire organizations around an inspiring purpose that drives superior performance.